Laporan Kasus: Orchiectomy Pada Anjing Penderita Cryptorrchid Bilateral - Tarsisius Considus Tophianong; Tri Utami (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
Cryptorrchid is the most common congenital defect found in dogs and cats. Cryptorrchid is a failure condition of one or both testicle to descend into the scrotum. On 2nd March 2019 an examination and treatment of two bilateral cryptorrchid’s dogs were done at the Praktik Dokter Hewan Bersama Grace Vetcare. The first patient’s identity is domestic dog, 3 years old, brown hairs, weigh 13 kg called name Iro. The second patient’s identity is domestic dog, 1.5 years old, brown hairs, weigh 15.5 kg called name Jacky. Based on physical examination and ultrasound examination, two dogs were diagnosed Bilateral Inguinal Cryptorrchid. Management treatment of both patients were done by orchiectomy operation. Orchiectomies were done by an open method, which is making incision in the left and right lateral inguinal region of the penis. This operation was done to minimize the risk of sertoli cell tumor (sertolioma). Orchiectomy is the only medical procedure that was recommended for cryptorchid treatment.